2014
DOI: 10.1016/j.ccr.2014.07.027
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer-Selective Targeting of the NF-κB Survival Pathway with GADD45β/MKK7 Inhibitors

Abstract: SummaryConstitutive NF-κB signaling promotes survival in multiple myeloma (MM) and other cancers; however, current NF-κB-targeting strategies lack cancer cell specificity. Here, we identify the interaction between the NF-κB-regulated antiapoptotic factor GADD45β and the JNK kinase MKK7 as a therapeutic target in MM. Using a drug-discovery strategy, we developed DTP3, a D-tripeptide, which disrupts the GADD45β/MKK7 complex, kills MM cells effectively, and, importantly, lacks toxicity to normal cells. DTP3 has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(139 citation statements)
references
References 43 publications
11
128
0
Order By: Relevance
“…Using three distinct models of solid cancers that are largely refractory to immunotherapies, including hepatocellular carcinoma (HCC) and ovarian adenocarcinoma, we showed that Gadd45b deletion in myeloid cells restores proinflammatory TAM activation and intratumoural CD8 + T-lymphocyte infiltration, resulting in diminished tumour growth. Since we previously showed that GADD45β additionally mediates the NF-κB antiapoptotic activity in cancer cells (24), our current findings identify GADD45β as a pivotal downstream hub integrating the NF-κB oncogenic functions linking cancer and inflammation. Our finding that elevated GADD45B expression correlates with poor clinical outcomes across most human cancers consolidates the general clinical significance of the GADD45β-mediated oncogenic mechanism in malignant disease.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Using three distinct models of solid cancers that are largely refractory to immunotherapies, including hepatocellular carcinoma (HCC) and ovarian adenocarcinoma, we showed that Gadd45b deletion in myeloid cells restores proinflammatory TAM activation and intratumoural CD8 + T-lymphocyte infiltration, resulting in diminished tumour growth. Since we previously showed that GADD45β additionally mediates the NF-κB antiapoptotic activity in cancer cells (24), our current findings identify GADD45β as a pivotal downstream hub integrating the NF-κB oncogenic functions linking cancer and inflammation. Our finding that elevated GADD45B expression correlates with poor clinical outcomes across most human cancers consolidates the general clinical significance of the GADD45β-mediated oncogenic mechanism in malignant disease.…”
Section: Introductionsupporting
confidence: 55%
“…We recently identified the product of the NF-κB-regulated gene, GADD45B , as an essential survival factor and novel therapeutic target in multiple myeloma (24). We therefore investigated whether GADD45B was involved in any types of malignancy beyond multiple myeloma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteasome inhibitor-resistant cell lines generated in vitro by continuous exposure to proteasome-inhibiting drugs serve as models to understand and potentially overcome proteasome inhibitor resistance. 14, 15, 16 Mutations in PSMB5 (encoding for β5c) were predicted to lead to impaired inhibitor binding owing to changes in the β5c active site or the inhibitor-binding pocket. 14, 17, 18 However, the functional relevance of such mutations on the active site binding of bortezomib or carfilzomib in MM cells has not been demonstrated, and extensive analysis in MM cells derived from patients resistant to proteasome inhibitor therapy failed to identify such PSMB5 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…The best documented function of NF-κB in cancer is to induce genes that block apoptosis and, despite its ubiquitous nature, NF-κB signaling elicits highly tissue-and context-specific transcriptional programs [66] . When compared to chemosensitive MM cell lines chemoresistant MM cells express higher levels of NF-κB, suggesting a link between NF-κB and development of chemoresistance [67] .…”
Section: Regulation Of Nf-κbmentioning
confidence: 99%